Development Aid as a Gift of Love: Re-inventing Aid on a Spiritual Foundation - Ulluwishewa, Rohana (Problemy Ekorozwoju, 2017)
Love, when viewed from quantum perspectives, is an outer manifestation of our interconnectedness at the quantum level. As revealed by recent discoveries in neuroscience, it is hardwired in our brain as a need to connect with others, serve others and act for others’ well-being. It is empowered to guide our actions only when we grow spiritually. Otherwise, we are mostly driven by self-centeredness, greed and fear soft-wired in the brain. This study points out that development aid is driven, not by love, but by self-centeredness, greed and fear in the minds of elites who control the global economic system. However, evidence show a spiritually developed population is slowly rising and alternative forms of aid driven by love are emerging. This study highlights the significance of re-inventing development aid on a spiritual foundation and presents some necessary policy measures.